Strategi Pelayanan Kesehatan Yang "Pro Publik" bagi Rumah Sakit - Hermawan, Hermawan (Jurnal Review Politik, 2016)
Health service policy at health sector in Indonesia was not yet considered as friendly to the public (or pro-public). Regulations had been released by the government to produce a just and apportion health service. However, in reality, health service with good quality was only enjoyed by some users who were financially afforded. Poor community found only difficulty when the demand of being served was emerging. Research was aimed to present alternative strategy of how to synchronize the demands for hospital-based service managerial structure that was efficient and effective in meeting the needs of whole community layers. The method of research was deductive approach. The application of this approach was combined with the content of analysis after it was subjected against the result of research. Type of research was comparative study. The result of research indicated that health service in the hospital could be improved in such way that the community would enjoy feasible health service. The structural component of health system in the hospital could adopt egalitarian component of health service. It was important component that could produce health product with a character of being pro-public service.